Vectors, Stages and Problems of Nonortodoxal Foundations of Economic Science Formation - Ya. S. Yadgarov; D. R. Orlova (Финансы: теория и практика)
The relevance of the study is underpinned by continuing sharp scientific and practical discussion on the evolution of economic science aimed at obtaining exhaustive answers to such questions as: “What is orthodoxy in economic science? Why is it that the theoretical and methodological orthodoxy that accompanies the emergence and transformation of alternative directions of world economic thought cannot be overcome not only in the past but also at the present time? What is the historical significance of a retrospective analysis of vectors, stages and problems of the formation of unorthodox foundations in the development of this branch of human knowledge? and others. The findings of prominent Russian and foreign scientists-economists, allowing to reveal and comprehend the diverse methodological and theoretical components of orthodoxy in the past and present set the subject of this review article. The purpose of the study is to consider, systematize and generalize the evidentiary warnings published in the works of prominent modern researchers about the urgent need to overcome the negative consequences of orthodox maxims, which, having been absolutized since the time of the “fathers of political economy”, continue to manifest themselves to this day. The key research methods include systematic approach, evolutionary and cross-industry analysis. The results of the review incorporate conclusions and evidence that make it possible to unbiasedly comprehend the key scientific and practical problems for the fate of this science in the past and present. In particular, the author’s position is argued that the examples of postulating judgments about the presence and coexistence of “Western-non-Western”, “bourgeoisnon- bourgeois” economic science, which are still found in Russian economic literature, are based solely on the classformational research approach and therefore are completely untenable. It has been proved that from its “ancestors” and “fathers” of economics, i. e. adherents mercantilism and classical political economy principles to modern economists (from institutionalists to Keynesians and neoliberals) the existing palette of orthodox theoretical and methodological innovations accompanying the development of economic science explicitly or implicitly along with its commitment to the class analytical approach are due to a certain subtext of the absolutization of “objective economic laws”.